Performa Produksi dan Kualitas Telur Ayam Petelur pada Sistem Litter dan Cage dengan Suhu Kandang Berbeda - Setiawati, T.; Afnan, R.; Ulupi, N. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Housing temperature and housing system may influence productive performance and egg qualities. This research aimed to investigate the influence of different housing temperatures and housing system on productive performance and egg qualities. A total of 72 Lohmann hens were reared in litter and cage system with different housing temperatures of 18oC and 30oC. Each treatment consisted of 18 hens. Traits measured were productive performance (feed intake, hen day production, egg weight, egg mass, and feed conversion), egg internal and external qualities (egg shape index, Haugh Unit, air sack, albumin height, egg shell cleanless, egg shell thickness, and egg shell weight).  This experiment was run twice according to housing system for each housing temperatures and was completely randomized design. Data was subjected to t-test and descriptive analyses. Productive production and egg quality in both housing systems did not differ. However, the egg weight was significantly heavier in cage system compared to litter system in neutral housing temperature.